PENGARUH FAKTOR PROMOSI, KUALITAS PRODUK, DAN KETIDAKPUASAN TERHADAP PERPINDAHAN MEREK - CANDRA, JOHAN (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: Nokia is a mobile phone vendors who famous in the world. On 2012 Nokia experienced a significant decline in sales compared to the year of 2011 The purpose of this study was to determine the effect of promotion, product quality and dissatisfaction on brand switching ofNokia mobile phones. The sample of the study was a Nokia mobile phone users who switch phone to another mobile phone brand ammounting100 people. Analysis using multiple regression analysis. The results of this study indicate that the promotion and dissatisfaction positive significant effect on brand switching mobile phones Nokia. While the quality of the products has a significant negative effect on brand switching of Nokia mobile phone. Keywords: promotion, product quality, dissatisfaction, brand switching.